1995
DOI: 10.1007/bf00511235
|View full text |Cite
|
Sign up to set email alerts
|

Core temperature thresholds for hyperpnea during passive hyperthermia in humans

Abstract: Humans have higher ventilation when they are hyperthermic but it is not known whether core temperature thresholds for ventilation exist, nor has a physiological rationale been presented for this response. To examine this question, ventilation was studied in relation to core temperatures in humans rendered hyperthermic in a warm bath. Seven subjects [mean (SE), 23.3 (1.4) years] wearing only shorts and a thick felt hat with ear flaps were immersed to the neck in a bath at 41 (0.5) degrees C for 25 min. Tympanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
90
3
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 24 publications
14
90
3
1
Order By: Relevance
“…3) is in agreement with results from previous studies (2,25). Petersen and Vejby-Christensen (25) suggested that a core temperature threshold for ventilation existed around 38°C above which a significant hyperpnea was evident.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…3) is in agreement with results from previous studies (2,25). Petersen and Vejby-Christensen (25) suggested that a core temperature threshold for ventilation existed around 38°C above which a significant hyperpnea was evident.…”
Section: Discussionsupporting
confidence: 92%
“…During the hyperthermic hypoxic exercise condition, V T increased in a relatively equal magnitude as during the normothermic hypoxic condition, yet the HVR was enhanced. This can be attributed primarily to the elevated f v as a result of the increased T es , which has been described as a thermal tachypnea (2,22). This supports the suggestion that an elevated T es influences the sensitivity of the peripheral chemoreceptors and helps explain the elevated HVR during hyperthermic exercise (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Since some studies have shown that thermally induced ventilatory responses are associated with increases in tidal volume, 8,31 we cannot exclude the possibility that our subjects also increased tidal volume. However, if we recalculate ventilatory heat loss using our breathing frequency data, and tidal volume changes from the existing literature (900 ml at a mean body temperature of 39.01C 8 ), we still obtain an almost identical outcome.…”
Section: Discussionmentioning
confidence: 98%